Upaya Meningkatkan Minat dan Hasil Belajar IPA Menggunakan Model Pembelajaran Problem Based Learning di MTs Negeri 7 Sleman - Astuti, Rita (Jurnal Pendidikan Madrasah, 2024)
This study is classroom action research, aiming to find out whether the PBL learning model can increase students' interest and learning outcomes in science at MTs Negeri 7 Sleman. This research was carried out in two cycles which included planning, action, observing, and reflection activities which were carried out in two cycles. The subject of the study is 7th grade students. Data collection uses observation methods with checklist instruments and performance tests. The data obtained were analyzed descriptively. The results of the study showed the completeness of classical learning outcomes in the first cycle, namely with an average score of 67.24 and 55.17% (16 students) with the complete category, while in the second cycle there was an increase with an average score of 80.11 and 84.62% (22 students) with the complete category. The conclusion of this study is that the PBL learning model can improve the learning outcomes of students with science material at MTs Negeri 7 Sleman.